Second Pillars : Provider and Product Selection for Funded Individual Accounts - World Bank (Washington, DC, 2012)
There are many ways to structure mandatory private pension funds that rely on individual accounts. As in any market there are products and firms that provide them. Both are typically circumscribed by the government for public policy reasons. Relevant legislation will specify the agent responsible for making key choices as to who manages the money and where it is invested. As discussed below, the focus of decision-making in funded schemes varies widely with potentially important implications for the performance of the scheme. In the context of mandated private pensions, this note looks at what investment and withdrawal products can be offered, who can offer them, and who chooses from among the alternatives available in this market.